A visible-light photoredox-catalyzed four-component reaction for the construction of sulfone-containing quinoxalin-2(1H)-ones. Issue 19 (9th August 2021) - Lv, Yufen; Luo, Jinyun; Lin, Muze; Yue, Huilan; Dai, Bin; He, Lin
Abstract : A visible-light photoredox-catalyzed four component reaction of quinoxalin-2(1 H )-ones, alkenes, aryldiazonium, and sodium metabisulfite leading to sulfone-containing quinoxalin-2(1 H )-ones has been developed. Abstract : A simple and efficient visible-light photoredox-catalyzed four component tandem reaction of quinoxalin-2(1 H )-ones, alkenes, aryldiazonium, and sodium metabisulfite has been developed at room temperature. Using rose bengal as a photocatalyst and under irradiation with 3 W blue LEDs, a number of sulfone-containing quinoxalin-2(1 H )-ones could be conveniently synthesized in moderate to good yields. A possible radical reaction pathway involving photocatalysis is proposed.